2012
DOI: 10.1155/2012/517976
|View full text |Cite
|
Sign up to set email alerts
|

Age at Diagnosis and Breast Cancer Survival in Iran

Abstract: Background. Tumour characteristics are the most important prognostic factors in breast cancer. Patient-related factors such as young age at diagnosis, obesity, and smoking behaviour may also modify disease outcome. Due to the absence of a unique definition for “young age breast cancer” and the resulting variation in disease management, findings on the association between young age and prognosis of breast cancer are controversial. Methods. This study included 1500 patients with a primary diagnosis of breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
5
22
1
Order By: Relevance
“…Although some findings (Vostakolaei et al, 2012) did not show significant association between survival and age, our results showed otherwise. Patients younger than 40 years old had lower survival compared to patients older than 40 years.…”
Section: Discussioncontrasting
confidence: 90%
“…Although some findings (Vostakolaei et al, 2012) did not show significant association between survival and age, our results showed otherwise. Patients younger than 40 years old had lower survival compared to patients older than 40 years.…”
Section: Discussioncontrasting
confidence: 90%
“…They studied 1500 patients at 6 hospitals in 5 provinces of Iran. The results indicated that the 5-year survival rate was 71% (25). Furthermore, Vahdaninia and Montazeri (2004) measured the total 5-year survival rate to be 62%, while in our study, it was reported to be 85% (26).…”
Section: Discussionsupporting
confidence: 47%
“…Most of the currently available data indicate that young age is associated with a poor prognosis due to the presence more invasive disease among this population[6, 7, 1013], which is supported by other studies[8, 9, 14], although some studies have noted that elderly women experience poorer outcomes than younger patients[15, 16]. …”
Section: Introductionmentioning
confidence: 59%